Confused or Deliberative: Narratives About the Birth of Islam in Polish History Textbooks - Katarzyna Górak-Sosnowska (Ignatianum University Press, 2024)
Objectives of the research: The aim of the article was to identify and analyse problematic areas related to how early Islam is presented and narrated in history textbooks, taking into account the local context. Research methods: The data corpus consists of 12 history textbooks. The mixed methods approach applied in the study included cluster analysis and discourse analysis. A brief description of the context of the issue: Islam and Muslims occupy limited space in the Polish school curricula, yet there is a plethora of information about the Islamic world in the public discourse. This puts a tremendous challenge on the shoulders of teachers and textbook authors to accurately present information about Islam and Muslims in schools. Research findings: Three problematic areas were discovered and analysed: (a) narrating Islam from a mainstream, non-Muslim perspective, which in the Polish case might be skewed into presenting Islam through the lens of Catholicism; (b) navigating between historical accounts and legends whilst presenting early Islam; and (c) explaining past events by interpreting them through contemporary events. Conclusions and recommendations: The article concludes by indicating challenges of teaching different religions in a largely mono-religious school setting, from the perspective of the classroom majority and Muslim students. Due to the marginal presence of Muslims in the public sphere, these narratives call for a more balanced approach. Otherwise, they can only further alienate and otherise Muslim students in the classrooms - and Islam in mainstream society.